Policy of Permission of Permit To Exit Indonesia’s Region In Immigration Perspective - Syakir (Journal of Social Science, 2020)
In the Immigration Law No. 6 of 2011 concerning Immigration Immigration is the matter of the traffic of people entering and leaving the Indonesian Territory and its supervision in order to maintain the upholding of the country's sovereignty, in the sense that we need to underline the word traffic, in immigration means synonymous with the movement of people, when speaking history at the beginning of the leadership of the immigration department at the time of the transition from the Dutch government to the Indonesian government adheres to the immigration law policy is open (open door) to selective (selective policy) for the national interest, in the case of traffic there is an inspection carried out by immigration officials who have absolute authority in carrying out their functions to provide entry or exit signs for Indonesian Citizens and Foreign Citizens (Foreigners) . Immigration checks by immigration officials facts in the field not all who want to enter or exit must be given permission, of course there is a legal basis or discretion in the implementation, for example when the departure of Indonesian citizens who want to work abroad and foreigners want to leave the territory of Indonesia, are prevented each month on departure, selective policy policies have a security and prosperity approach in that they can not only screen people who want to come to the Region Indonesia, based on the data obtained by researchers that there will be an explanation in there is a policy (selective policy) which we have been unaware of and we have applied for a long time that a selective policy exists on departure which results in people not getting an exit sign and then prevented in the future. appointment.